Microwave and RF Design Amplifiers and Oscillators - Steer, Michael (Open textbook library., 2019)
Microwave and RF Design: Amplifiers and Oscillators presents the design of amplifiers and oscillators in a way that enables state-of-the-art designs to be realized. Detailed strategies and case studies are presented. Design of competitive microwave amplifiers and oscillators is particularly challenging as many trade-offs are required in design, and the design decisions cannot be reduced to a formulaic flow. The emphasis is on developing design skills. This book is suitable as both an undergraduate and graduate textbook, as well as a career-long reference book.